Great expectations - Dickens, Charles (Literature)
The orphan, Pip, and the convict, Magwitch, the beautiful Estella, and her guardian, the embittered and vengeful Miss Havisham, the ambitious lawyer, Mr. Jaggers -- all have a part to play in the mystery